SOSIO-RELIGIUS PESANTREN: AKTUALISASI NILAI-NILAI AGAMA DALAM RUANG SOSIAL KEMASYARAKATAN DI LOMBOK TIMUR - Muhammad War'i (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This paper discusses the socio-religious attitude of the pesantren which is manifested by the Islamic Boarding School Ma'had Darul Quran wal Hadith Al-Majidiyah As-Syafi'iyah Nahdlatul Wathan in a social context. Through the phenomenology approach, this research will elaborate on this. Islamic boarding schools are often represented by santri learning places with strict pesantren regulations. The santri stayed in certain locations (dormitories) with 24-hour caregiver supervision. This fact often leaves “empty spaces” in the form of